Peningkatan Kemampuan Sosial Emosional Anak Usia 5-6 Tahun melalui Kegiatan PHBS (Perilaku Hidup Bersih dan Sehat) di BKB PAUD Pelangi Jakarta Timur - Swastika, Kim; Kasih, Delina; Rahayu, Wening (INTELEKTIUM, 2025)
Enhancing Positive Character of Children Aged 5-6 Years Through Clean and Healthy Living Behavior (PHBS) Activities at BKB PAUD Pelangi, East Jakarta (2025). Undergraduate Thesis. Jakarta: Universitas Panca Sakti Bekasi. 2025. This study aims to enhance the positive character of children aged 5-6 years through Clean and Healthy Living Behavior (PHBS) activities at BKB PAUD Pelangi, East Jakarta. The development of positive character in early childhood serves as an essential foundation for personality growth that will influence their future life. PHBS activities were chosen as a learning medium because they integrate physical health aspects with character building through the habituation of positive daily behaviors. The research method used was Classroom Action Research (lCAR) with the Kemmis and McTaggart model, carried out in two action cycles. Eachl cycle consisted of planning, implementation, observation, and reflection stages. Data were collected through observation, interviews, and documentation.The results showed that consistent and structured PHBS activities can foster the development of positive character traits in children, such as discipline, responsibility, independence, and environmental awareness. The habituation of PHBS not only improves children’s health but also stimulates the development of positive character from an early age. This research concludes that PHBS can serve as an effective strategy to improve positive character of young children in educational settings.